BENIGN PROSTATIC HYPERPLASIA - Citra Gading; Gede Wirya Kusuma Duarsa (Bali Journal of Medical and Health Sciences, 2013)
Benign Prostatic Hyperplasia (BPH) is a nonmalignant enlargement of the prostate gland. BPH is commonly found in elderly man. The clinical manifestation include Lower Urinary Tract Syndrome (LUTS), Bladder Outlet Obstruction (BOO), acute and chronic urinary retention, urosepsis, urinary tract infection, bladder stone, and hematuria. BPH is diagnosed based on history taking, physical examintaion, rectal examination, laboratory examination, and urinary flow rate. Management of BPH based on patient symptom, include watchful waiting, medical therapy, minimally invasive therapy, and surgical therapy. Key words: Benign Prostatic Hyperplasia (BPH), Lower Urinary Tract Syndrome (LUTS), Prostate, Urethra